1998
DOI: 10.1093/brain/121.12.2301
|View full text |Cite
|
Sign up to set email alerts
|

Functional mapping of human sensorimotor cortex with electrocorticographic spectral analysis. II. Event-related synchronization in the gamma band

Abstract: It has been shown in animals that neuronal activity in the 'gamma band' (>30 Hz) is associated with cortical activation and may play a role in multi-regional and multi-modal integration of cortical processing. Studies of gamma activity in human scalp EEG have typically focused on event-related synchronization (ERS) in the 40 Hz band. To assess further the gamma band ERS further, as an index of cortical activation and as a tool for human functional brain mapping, we recorded subdural electrocorticographic (ECoG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

89
778
5
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 966 publications
(893 citation statements)
references
References 35 publications
89
778
5
5
Order By: Relevance
“…Increases in HFB change were focused on primary sensorimotor electrodes during movement (Figs. 1, 2, and 5), consistent with previous studies [Crone et al, 1998a;Leuthardt et al, 2007;Miller et al, 2007;Miller et al, 2009b]. This high frequency spectral power change has been shown to correlate directly with firing rate [Manning et al, 2009;Miller et al, 2009a;Whittingstall and Logothetis, 2009], and has been demonstrated to reflect broadspectral change across all frequencies Miller et al, 2009b].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Increases in HFB change were focused on primary sensorimotor electrodes during movement (Figs. 1, 2, and 5), consistent with previous studies [Crone et al, 1998a;Leuthardt et al, 2007;Miller et al, 2007;Miller et al, 2009b]. This high frequency spectral power change has been shown to correlate directly with firing rate [Manning et al, 2009;Miller et al, 2009a;Whittingstall and Logothetis, 2009], and has been demonstrated to reflect broadspectral change across all frequencies Miller et al, 2009b].…”
Section: Discussionsupporting
confidence: 88%
“…They have shown that broadband power increases, revealed at high frequencies, are typically local, on areas primarily involved in the task [Crone et al, 1998a;Miller et al, 2009b], and these high frequency changes correspond well to sites found with electrocortical stimulation of language and motor regions Sinai et al, 2005]. Power decreases in low frequency sensorimotor rhythms are distributed over larger areas of cortex [Crone et al, 1998b;Miller et al, 2007].…”
Section: Introductionmentioning
confidence: 53%
“…The observations in the present study using electrical stimulation are consistent with those reported in previous studies using fMRI (Yousry et al, 1997), MEG (Kristeva et al, 1991) and intracranial EEG (Crone et al, 1998). Previous neuroimaging studies using fMRI and [15O]-water PET demonstrated that motor tasks such as finger tapping or hand grasping consistently activated the contralateral post-central gyrus defined by anatomical landmarks, in addition to the precentral, premotor and supplementary motor areas (Yousry et al, 1997).…”
Section: Evidence From Activation Studies Using Fmri Meg and Intracrsupporting
confidence: 92%
“…Similarly, previous studies using MEG coregistered to MRI demonstrated that a large-amplitude motor task-evoked magnetic field was localized to the contralateral postcentral gyrus in healthy volunteers (Kristeva et al, 1991). A previous study of adults with focal epilepsy using intracranial EEG recording and each individual's brain surface image demonstrated that gamma-band EEG power was increased in both pre-and postcentral gyri about 200−500 ms after the onset of contralateral fist-clenching (Crone et al, 1998).…”
Section: Evidence From Activation Studies Using Fmri Meg and Intracrmentioning
confidence: 63%
“…In humans, high gamma power ECoG responses following movements of different body parts were found to occur in a more discrete topographical pattern than the beta ERD phenomena. Furthermore, somatotopically defined regions on the basis of high gamma oscillations in the sensorimotor cortex were consistent with maps generated by cortical electrical stimulation (Crone et al, 1998b). Furthermore, another study on 4 epileptic patients performing a face detection task showed a good spatial colocalization between the increase of high gamma band SEEG activity and the results from the fMRI literature using different but comparable tasks (Lachaux et al, in press).…”
Section: Erps and Seeg In The Beta Frequency Do Not Colocalize With Tsupporting
confidence: 73%